An emerging and novel approach toward Pro-poor tourism: a study of homestays in Sittong, Darjeeling, India - Pradhan, Shailendra Mani (Frontiers in Sustainable Tourism, 2024)
IntroductionTourism has an important influence on shaping the development trajectory of communities, particularly in developing countries. Given its economic significance and social implications, tourism constitutes an integral part of the development intervention of government and other agencies. This research examines homestays in Sittong, Darjeeling Himalaya, India, through the lens of Pro-poor tourism. The study looks at the impact of homestay tourism on rural mountain communities vis-à-vis livelihoods and environmental sustainability, with a focus on how tourism benefits are distributed or shared among different socio-economic groups.MethodsThe study is based on the interpretivist paradigm. Data were gathered through in-depth interviews and focus group discussions (FGD) with homestay owners, helpers, nature guides, local community members, and public officials. A total of fifteen locally owned homestays were surveyed, including thirty personal interviews and one FGD. Thematic analysis was utilized to analyze the data.ResultsHomestays are rapidly changing the contours of rural livelihoods in Sittong by producing significant economic benefits for various socio-economic groups, enhancing community engagement, and strengthening the Pro-poor tourism strategy. However, challenges such as bureaucratic barriers, government apathy, non-local ownership of homestays, and environmental degradation impede progress toward pro-poor goals and sustainable tourism.DiscussionThis research emphasizes the significance of inclusive decision-making, capacity building, financial support, and sustainable practices in addressing livelihood issues and environmental sustainability in rural mountain communities. The study calls for a balanced approach that integrates economic growth, social equity, and environmental sustainability to ensure the long-term success of homestay tourism in the Darjeeling Himalaya and other similar settings.